Diseases of ber (Zizyphus jujube) in Eastern India (The Journal of Plant Protection Sciences, 2023)
Ber (Zizyphus mauritiana Lamk - Rhamna ceae) is one of the important fruit crops of  arid and semi arid zones of the world. In India  though it is a minor fruit but recently the ber  become an important cash crop in some areas  and its acreage and production are increased.  Due to rapid spread of commercial cultiva tion, the crop is also affected by different bi otic and abiotic factors including pathogens  causing many serious diseases. Not much at tention to the diseases of ber has been given  so far and remained under-estimated the prob lems. The ber, a tropical fruit crop is prevalent  in arid and semi-arid region of the world. The  crop considered as minor fruit in this country  on the basis of its production in restricted  area, popularity and awareness although it is a  very important crop and contributes a good  share of economy in many localities. Several  biotic and abiotic stresses have been responsi ble for causing diseases, related to loss of  crop. As the importance of the crop generally  continue in a locality or a particular state thus  it overlooks the national importance particu larly researches on protection technology,  leading to limited knowledge for management  of different diseases both in pre-harvest as  well as post-harvest stage. Ber is affected by  many serious diseases like powdery mildew,  sooty mold, leaf spots (Alternaria, Cerco spora, Septoria, Cladosporium, Pestalo tiopsis etc.) and rust among the fungal infec tions and witches broom caused by MLOs as  reported by Jamader et al. (3). Seven diseases  on ber were identified by Yuan et al. (7) in  China mostly grown in the southern provinces  of the country and also grown in India. While  many diseases originated in the orchards, fruit  rot may initiates from the filed and may ex press in storage due to lack of proper handling  and storage conditions. The amount of loss  caused by fruit diseases is tremendous and has  not yet been documented properly and thus  adoption of suitable remedial measure is  needed. The present investigation was carried  during 2010-11 to identify the diseases preva lent in ber and also to find out seasonal varia tion of different diseases.
Keywords: Extensive survey; abiotic; documented